Psychological factors in organizations evaluation - Deciu, Valeriu (Advances in Social Sciences Research Journal, 2021)
When major corporate breaches have occurred, the blame and the punishment always has been on the so-called “bad apples” in an organization. The trouble with such an approach ignores the cultural and psychological context about which the “bad apple” flourishes. Usually, corporate breaches seem to occur in two areas; they will either involve ethical or legal violations. An understanding of ethical and compliance issues in an organization is thus of utmost importance. These issues herein inspired research. The concern of the study will be the psychological factors within an organization that need understanding from an ethical or compliance point of view.